D-Glucosamine production from chitosan hydrolyzation over a glucose-derived solid acid catalyst. Issue 10 (1st February 2018) - Zhang, Hongkui; Lu, Yuting; Wang, Yuanhao; Zhang, Xingrong; Wang, Tingyu
Abstract : A method for preparingd -glucosamine in aqueous phase by chitosan degradation by a solid acid, which resulted in high yields. Abstract : A glucose-based solid acid catalyst (GSA) was synthesized by hydrothermal carbonization and its physicochemical properties were explored by various characterization techniques including IR, TG and SEM. In addition, its catalytic performance towardsd -glucosamine formation from the hydrolysis of chitosan was extensively investigated to determine the effects of reaction parameters, such as reaction temperature, time and mass ratio of catalyst and reactants. The experimental results revealed that the yield of targeted productd -glucosamine could reach as high as 98.1% under optimal conditions (temperature: 110 °C; time: 6 h). After six catalytic cycles, no evident deactivation was observed, suggesting the satisfactory stability of the investigated solid acid catalyst. This might provide insight on the development of suitable catalyst systems ford -glucosamine formation to replace homogeneous catalysts.